In vivo bone regeneration assessment of offset and gradient melt electrowritten (MEW) PCL scaffolds - Naghmeh Abbasi; Ryan S. B. Lee; Saso Ivanovski; Robert M. Love; Stephen Hamlet (Biomaterials Research, 2020)
Abstract Background Biomaterial-based bone tissue engineering represents a promising solution to overcome reduced residual bone volume. It has been previously demonstrated that gradient and offset architectures of three-dimensional melt electrowritten poly-caprolactone (PCL) scaffolds could successfully direct osteoblast cells differentiation toward an osteogenic lineage, resulting in mineralization. The aim of this study was therefore to evaluate the in vivo osteoconductive capacity of PCL scaffolds with these different architectures. Methods Five different calcium phosphate (CaP) coated melt electrowritten PCL pore sized scaffolds: 250 μm and 500 μm, 500 μm with 50% fibre offset (offset.50.50), tri layer gradient 250–500-750 μm (grad.250top) and 750–500-250 μm (grad.750top) were implanted into rodent critical-sized calvarial defects. Empty defects were used as a control. After 4 and 8 weeks of healing, the new bone was assessed by micro-computed tomography and immunohistochemistry. Results Significantly more newly formed bone was shown in the grad.250top scaffold 8 weeks post-implantation. Histological investigation also showed that soft tissue was replaced with newly formed bone and fully covered the grad.250top scaffold. While, the bone healing did not happen completely in the 250 μm, offset.50.50 scaffolds and blank calvaria defects following 8 weeks of implantation. Immunohistochemical analysis showed the expression of osteogenic markers was present in all scaffold groups at both time points. The mineralization marker Osteocalcin was detected with the highest intensity in the grad.250top and 500 μm scaffolds. Moreover, the expression of the endothelial markers showed that robust angiogenesis was involved in the repair process. Conclusions These results suggest that the gradient pore size structure provides superior conditions for bone regeneration.